2017
DOI: 10.12659/msm.906959
|View full text |Cite
|
Sign up to set email alerts
|

The Function of the Novel Mechanical Activated Ion Channel Piezo1 in the Human Osteosarcoma Cells

Abstract: BackgroundThe Piezo1 protein ion channel is a novel mechanical activated ion channel which is related to mechanical signal transduction. However, the function of the mechanically activated ion channel Piezo1 had not been explored. In this study, we explored the function of the Piezo1 ion channel in human osteosarcoma (OS) cells related to apoptosis, invasion, and the cell proliferation.Material/MethodsReverse transcription polymerase chain reaction (RT-PCR) and western-blotting were used to detect the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Hypoperfusion and hypoxia lower the efficacy of tumour targeted drug delivery, promoting immune evasion and tumour metastasis. Evidence has shown that expression of PIEZO1 increased in multiple malignant diseases including bladder carcinoma, synovial sarcoma, osteosarcoma, breast cancer and gastric cancer 12,[46][47][48][49] . PIEZO1 is also involved in 2D cell migration and 3D invasion in the MCF-7 cell line, a gastric cancer cell line, and small-cell lung carcinoma cell lines 12,33,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoperfusion and hypoxia lower the efficacy of tumour targeted drug delivery, promoting immune evasion and tumour metastasis. Evidence has shown that expression of PIEZO1 increased in multiple malignant diseases including bladder carcinoma, synovial sarcoma, osteosarcoma, breast cancer and gastric cancer 12,[46][47][48][49] . PIEZO1 is also involved in 2D cell migration and 3D invasion in the MCF-7 cell line, a gastric cancer cell line, and small-cell lung carcinoma cell lines 12,33,49 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, further in vivo experiments demonstrated that the suppression of Piezo1 gene expression enhanced tumor growth of such cells in immunocompromised mice. In brief, the results obtained in this study showed an oncosuppressive role for Piezo1 through Ca 2+ -induced apoptosis and the inhibition of the proliferative capability of OS cells [88].…”
Section: Osteosarcomamentioning
confidence: 52%
“…OS is often associated with aberrant mechanical features [87], thus, it is reasonable considering that MS channels, especially Piezo channels, may play an essential role in OS tumorigenesis. In a study carried out by Jiang and colleagues, Piezo1 channels were found overexpressed in human OS cells [88]. The data of in vitro experiments indicated that Piezo1 could mediate the mechanical stress, inducing apoptosis and inhibiting cell proliferation of OS cells.…”
Section: Osteosarcomamentioning
confidence: 97%
“…In addition, Piezo channel activation can deliver local Ca 2+ influx, thereby modulating key Ca 2+− dependent signaling pathways associated with cancer cell migration, proliferation, and angiogenesis (De Felice and Alaimo, 2020). Recent studies have noted the close correlation between the Piezo1 channel and some cancers, including gastric cancer, oral squamous cell carcinoma, prostate cancer, colon cancer, synovial sarcoma, and osteosarcoma (Jiang et al, 2017;Suzuki et al, 2018;Zhang et al, 2018;Han et al, 2019;Sun et al, 2020;Hasegawa et al, 2021;Wang et al, 2021). Piezo1-dependent mechanosensation has also been linked to immune regulation in the differentiation of suppressive myeloid cells that regulate cancer and infectious diseases (Aykut et al, 2020).…”
Section: Future Outlookmentioning
confidence: 99%